Dual Pathologies: Pial Arteriovenous Fistula in Combination with an Arteriovenous Malformation - Jannelli, Gianpaolo; Joswig, Holger; Bernava, Gianmarco; Meling, Torstein R.; Bijlenga, Philippe (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background A pial arteriovenous fistula (PAVF) is a rare neurovascular pathology consisting of a direct connection between one or more arterial feeders and a single venous channel. A PAVF was previously considered a subtype of an arteriovenous malformation (AVM). In the current literature these are distinguished as two independent entities with different clinical, physiopathologic, and structural characteristics. We report a case of a surgically treated 37-year-old woman with an extremely rare combination of an unruptured PAVF and AVM.Patient The AVM was mainly supplied by feeders of the middle cerebral artery and drained into the sigmoid sinus via an abnormally dilated and tortuous vein. Following its resection, intraoperative digital subtraction angiography (DSA) in the hybrid operating room revealed the presence of a PAVF that had not been noted during the preoperative planning. Hence the PAVF was completely disconnected as confirmed by DSA again.Conclusion This is the second reported case of an AVM-associated PAVF. Without the intraoperative DSA in the hybrid operating room, this unusual complex cerebrovascular entity would likely have been missed.
Keywords: arteriovenous malformation; augmented reality; hybrid operating room; pial arteriovenous fistula